VOICES: the value of 6-month clinical evaluation in stroke. The protocol for a planned qualitative study to ascertain the value of stroke follow-up to people affected by stroke. Issue 10 (28th October 2014) - Jenkins, Colin; Price, Fiona
Abstract : Introduction: The National Clinical Guidelines for Stroke recommend 'routine follow-up of patients 6 months post discharge'. The Sentinel Stroke National Audit Programme sets a standard of 6 months postadmission follow-up, capturing data on process and outcomes. There appears to be no convincing model of stroke follow-up at 6 months, and despite evidence of unmet need in almost 50% of stroke survivors 1–5 years after their stroke, little work focuses on the first 12 months of recovery. By listening to the living experiences of stroke, the research aims to tailor the stroke care pathway to the needs of those affected. Methods and analysis: A focus group of six stroke survivors and carers will be invited to identify appropriate interview questions about the value of follow-up at 6 months, ensuring that this study has its genesis in the participant experience. A pilot study of four stroke survivors will ascertain the feasibility of the method. Thirty stroke survivors from the follow-up clinic will be invited to take part in semistructured interviews. Raw data, in the form of digital recordings of the interviews, will be transcribed. Interview transcriptions will be checked by the participant for accuracy prior to analysis using NVivo software. Literal and reflective narrative analysis will be used to code transcribed text to examine shared themes and reflect on content. Ethics and dissemination: Study documentation has been reviewed by the Coventry and Warwickshire Research Ethics Committee; the chief investigator met with the committee to scrutinise the study and justify its methodology. The committee has approved this study. A copy of the final report will be given to participants, the Stroke Association, the local Clinical Commissioning Group and participants' general practitioners. It is intended to disseminate the results locally by presentation to the Trust board, at academic conferences and by publication in a peer-reviewed scientific journal.